2007
DOI: 10.1109/jlt.2006.887185
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of Pulses to c/10 With Subwatt Power Levels and Low Latency Using Brillouin Amplification in a Bismuth-Oxide Optical Fiber

Abstract: Abstract-We report the generation of slow light using Brillouin amplification in a short length of highly nonlinear bismuth-oxide fiber. By using just 2 m of fiber, we demonstrate a five-fold reduction in group velocity for ∼200-ns pulses, which we believe to be a record for a slow-light propagation in an optical fiber. Moreover, by virtue of the high nonlinearity per unit length of this fiber, we achieve this at a very modest pump power level of just ∼400 mW and with a low inherent device latency of 14 ns. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For the SMF transmission using the 80 kHz linewidth laser, the output power was severely limited by the SBS, and it was observed that the output power did not change as the input power increased when the power exceeded 120 mW. In SMF-28, the values of A eff and g B are shown as approximately 80 µm 2 and 1.3 × 10 −11 m −1 W −1 , respectively [17]. Substituting these values into Eq.…”
Section: Stimulated Brillouin Scattering (Sbs)mentioning
confidence: 98%
“…For the SMF transmission using the 80 kHz linewidth laser, the output power was severely limited by the SBS, and it was observed that the output power did not change as the input power increased when the power exceeded 120 mW. In SMF-28, the values of A eff and g B are shown as approximately 80 µm 2 and 1.3 × 10 −11 m −1 W −1 , respectively [17]. Substituting these values into Eq.…”
Section: Stimulated Brillouin Scattering (Sbs)mentioning
confidence: 98%
“…1 Among these nonlinear effects, the nonlinear inelastic scattering effects have attracted the most notable interest. [3][4][5][6] SBS as well as other nonlinear effects are very weak and require huge amounts of power and long fiber lengths. This process can be electrostrictively amplified and gives rise to stimulated Brillouin scattering (SBS).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly attributed to its numerous and unique advantages, such as its ability to create resonance at any wavelength by simply changing the pump wavelength, its operations at room temperature, and its excellent compatibility with the communication system available. To date, the SBS-based slow light in various fibers, including standard single-mode fibers, bismuth-oxide fibers [17], chalcogenide fibers [18,19], tellurite glass fibers [20,21], and photonic crystal fibers [22,23] has been investigated.…”
Section: Introductionmentioning
confidence: 99%